Severe filarial chyluria Managed successfully with sclerotherapy: A case report from Sudan - Eltahir Ahmed Eltahir; Ghassan Mahmoud Mohammed Yousuf; Walyeldin Elnour Mohamed Elfakey; Moneer Ali Abdallah; Muna Mohammed Ahmed Hamid Ahmed (Urology Case Reports, 2025)
Introduction: Chyluria is characterized by the passage of milky urine resulting from abnormal lymphatic drainage into the urinary tract. In parasitic cases, it is commonly caused by Wuchereria bancrofti and has varying severities. Diagnosis relies on clinical, laboratory, and radiological assessments, with treatment options spanning dietary modifications to surgical interventions. Case presentation: A 43-year-old male presented with chyluria for one year. He received medical treatment for filariasis without response. sclerotherapy with 5 % povidone Iodine was done successfully. Conclusion: Severe cases of chyluria can be treated successfully with povidone Iodine 5 %.